The foundations of Japan : - Scott, J. W. Robertson (John Murray, Albemarle Street, W., 1922)
Contents: studies in a single prefecture; the mostt exacting crop in the world; back to first principles the apostle and the artist; across Japan (Tokyo to Niigata and back); ....